The transformative leadership compass: six competencies for digital transformation entrepreneurship - Schiuma, Giovanni; Schettini, Eva; Santarsiero, Francesco; Carlucci, Daniela (International journal of entrepreneurial behaviour & research, 2022)
PurposeIn the digital age, companies require leaders to foster digital transformation entrepreneurship, i.e. the organisational attitude and orientation of the creation of a new business or the development of an existing business by having at the core or embracing digital transformation as the continuous development and application of digital knowledge for companies' value creation. This paper identifies six critical competencies distinguishing the transformative leadership profile supporting enterprises' digital transformation development.Design/methodology/approachThe paper, through a critical literature review focussing on three research streams, i.e. wise, transformative and digital leadership, addresses the following research question: What competencies characterise a digital transformative leader promoting and encouraging digital transformation entrepreneurship? Methodologically, first, explorative analysis of the literature has been carried out exploring the role and relevance of leadership in driving companies' digital transformation. Second, focussing on the three leadership perspectives, wise, transformative and digital, the critical features distinguishing each view have been identified. A set of hypotheses has been formulated to develop a framework to profile a digital transformative leader. In the third stage, the framework of the digital transformative leadership compass has been developed.FindingsThe paper profiles the digital transformative leader, a critical figure in companies competing in the digital age to nurture digital transformation entrepreneurship. Six specific competencies are synthesised and proposed throughout the transformative leadership compass. It is presented as an interpretative framework helpful to understand what affects the organisational culture and behaviours driving digital transformation. The proposed model defines theoretical foundations to operationalise an assessment framework and developing empirical research about leadership characteristics hampering and enabling successful companies' digital transformation.Originality/valueThe study proposes a novel framework based upon a critical analysis of the leadership literature. Combining insights gathered from the literature review on transformative, wise and digital leadership, the need for nurturing a transformative digital leadership allowing enterprises to stay competitive and able to change and adapt to the scenario's evolution emerged. Accordingly, the paper defines the digital transformative leader as a leadership profile sustaining organisational and digital transformation. The transformative leadership compass is proposed as a model to outline the critical competencies distinguishing a digital transformative leader capable of driving continuous company innovation and specifically digital transformation entrepreneurship.